Uncertain Technological Change under Capital Mobility - Paul A. de Hek (Tinbergen Institute, 2005)
The analysis in this paper shows that unpredictable variations in economic productivity may have a positive or negative effect on the average growth rate of output. This theoretical ambiguity result is not solely determined by the value of the elasticity of intertemporal substitution (of consumption) - as is the case in earlier analyses - but depends on two factors. That is, the growth-uncertainty relationship depends on whether returns to scale in knowledge creation are increasing or non-increasing and whether the elasticity of intertemporal substitution (of profits) is higher or lower than some critical value. Empirical studies concerning these two factors indicate that unpredictable variations in economic productivity have a negative effect on the average long-run growth rate.
Keywords: O3; 330; Long-run growth; Technological change; Uncertainty; Technischer Fortschritt; Produktivität; Kapitalmobilität; Wirtschaftswachstum; Risikoaversion; Neue Wachstumstheorie